Power Outage: A Simulation Case for Anesthesiology Residents - Luke Johnson; Ezoza Rajabaliev; Kristin Canipe; Michael R. Kazior (MedEdPORTAL)
Introduction Power outages in the OR are rare. However, anesthesia providers must be prepared to manage these situations until power is restored or their patient can be moved to a safe area. These situations occur so infrequently that many learners do not experience these events during their training. We designed a high-fidelity power outage simulation for anesthesiology residents to fill this training gap and enhance their preparedness and confidence. Methods In each simulation session consisting of up to four learners, one or two PGY 3/PGY 4 residents participated as anesthesiologists in a case involving an intraoperative power loss during a routine inguinal hernia repair of a patient under general anesthesia. After the simulation, residents received a debriefing focused on intraoperative power outage training. After concluding the debriefing, residents completed a 5-point Likert scale survey to assess their confidence in managing an intraoperative power loss. Results Over 2 years, 22 anesthesiology residents completed the simulation. Residents’ mean ratings of confidence in managing a patient in the OR during a power outage improved by 1.2 points (p =.001), confidence in monitoring vital signs improved by 1.4 (p = .001), and confidence in planning appropriate disposition improved by 0.9 (p =.001). All participants found the simulation highly valuable. Discussion The anesthesiology-specific simulation proved to be an effective educational tool. Feedback was positive as residents agreed that the simulation was valuable for developing clinical reasoning and decision-making skills, significantly boosting their confidence to respond effectively and maintain patient safety.